(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The Quadratic dynamical systems considered as an important source of analysis for the study of dynamical properties and modeling in various fields. A quadratic stochastic operator (in short QSO) is usually used to present the time evolution of species in biology. The general problem in the nonlinear operator theory is to study the behavior of operators. This problem was not fully finished even for quadratic stochastic operators which are the simplest nonlinear operators. To study this problem, several classes of QSO were investigated. In this paper we investigate the dynamics of three classes of such operators.